(untitled) (ALBACORE Jurnal Penelitian Perikanan Laut, 2026)
Capture od sharks as bycatch from tuna longliners, tuna handliners, and tuna gillneters based at Cilacap Ocean Fishing Port decreased 15% from 226.18 tons in 2020 to 192.62 tons in 2024. This study aims to analyze species composition and annual trends of shark production for each type of fishing fleet. This study was conducted from September to October 2024 at the Cilacap Ocean Fishing Port, Central Java. Data were obtained from port statistics covering Januari 2019 to December 2024. The average trip duration tuna longliners was 90 day while for tuna handliners and tuna gillneters were bb days and cc days, respectively. The fishing grounds of the tuna longliner were from 8°-15°LS and 101°- 110°E, while the tuna handliners were from 8°-14° S and 103°-109°E, and tuna gillneters from 8°-9°S and 108°-110°E. Dominant species of sharks captured by tuna longliners are hiu selendang (Prionace glauca), hiu lanjaman (Carcharhinus falciformis) dan hiu pahitan (Alopias superciliosus) while those caotured by tuna handliners and tuna gillneters were hiu tikusan (Alopias pelagicus), hiu pahitan (Alopias superciliosus), and hiu selendang (Prionace glauca). Key words: fishing fleet, Cilacap, fluctuation, sharks, composition